Avaliação do uso de indicadores para a caracterização da sustentabilidade da coleta seletiva de resíduos sólidos urbanos em Araraquara e São José do Rio Preto (SP) - Lemes, João Luiz Villas Boas (2015)
Urban solid waste management (MSW) is a growing challenge for municipal administrations in view of their increasing quantity and complexity. In Brazil, the National Solid Waste Policy (PNRS), approved in 2010, became a reference to foster local public policies, incorporating the concern with sustainability. Some authors have proposed sustainability indicators (IS) to evaluate selective collection (CS), since the sector lacks tools to assist in the decision making and more sustainable monitoring of waste picker organizations. The general objective of this research is to evaluate the use of indicators to characterize the sustainability of selective collection of MSW, having as object of study the cities of Araraquara and São José do Rio Preto. The research was based on the evaluation of PNRS, recycling, general aspects of SC in Brazil and identification of IS for selective collection. For the application, the IS sets, proposed by Besen (2011), were defined as the most appropriate for the evaluation of the SC and of the pickers' organizations, once they were constructed and validated in a participatory way. In 2014, the selective collections of the two municipalities investigated were monitored. The comparative result showed significant qualitative and quantitative differences in the execution of the SC and in the management of waste picker organizations, especially in the operational aspects. To apply the IS, some meetings were held in the two municipalities surveyed. These included municipal managers, technical staff and members of waste picker organizations. All proposed indicators were applied and evaluated, and some, due to difficulties in data collection and lack of proper monitoring, were only estimated. Based on the results of the IS, two sustainability matrices were built, one from the municipal SC and the other from the collector organizations for the two municipalities. The comparative result showed significant qualitative and quantitative differences in the execution of the SC and in the management of waste picker organizations, especially in the operational aspects. To apply the IS, some meetings were held in the two municipalities surveyed. These included municipal managers, technical staff and members of waste picker organizations. All proposed indicators were applied and evaluated, and some, due to difficulties in data collection and lack of proper monitoring, were only estimated. Based on the results of the IS, two sustainability matrices were built, one from the municipal SC and the other from the collector organizations for the two municipalities. The result of the IS application made it possible to calculate the respective sustainability indices. The index calculated for selective collection reached the favorable range for sustainability for both municipalities. For waste picker organizations, the Araraquara index reached the very favorable range for sustainability and, in São José do Rio Preto, the favorable range for sustainability. The similarity in sustainability indices for the two municipalities differed from the observation of CS monitoring in the field. The research concludes that it is necessary to build new IS sets and improve the evaluated IS set to improve the more sustainable management of selective collection with participatory social inclusion.